A high performance surface acoustic wave visible light sensor using novel materials: Bi2S3 nanobelts. Issue 15 (2nd March 2020) - Li, Chong; Kan, Hao; Luo, Jingting; Fu, Chen; Zhou, Jian; Liu, Xueli; Wang, Wen; Wei, Qiuping; Fu, Yongqing
Abstract : A high performance surface acoustic wave visible light sensor with Bi2 S3 nanobelts. Abstract : Low dimensional Bi2 S3 materials are excellent for use in photodetectors with excellent stability and fast response time. In this work, we developed a visible light sensor with good performance based on surface acoustic wave (SAW) devices using Bi2 S3 nanobelts as the sensing materials. The SAW delay-line sensor was fabricated on ST-cut quartz with a designed wavelength of 15.8 microns using conventional photolithography techniques. The measured center frequency was 200.02 MHz. The Bi2 S3 nanobelts prepared by a facile hydrothermal process were deposited onto SAW sensors by spin-coating. Under irradiation of 625 nm visible light with a power intensity of 170 μW cm −2, the sensor showed a fast and large response with a frequency upshift of 7 kHz within 1 s. The upshift of the frequency of the SAW device is mainly attributed to the mass loading effect caused by the desorption of oxygen from the Bi2 S3 nanobelts under visible light radiation.